In-hospital mortality among consecutive patients with ST-Elevation myocardial infarction in modern primary percutaneous intervention era ~ Insights from 15-year data of single-center hospital-based registry ~. - Kensuke Takagi; Akihito Tanaka; Naoki Yoshioka; Yasuhiro Morita; Ruka Yoshida; Yasunori Kanzaki; Naoki Watanabe; Ryota Yamauchi; Shotaro Komeyama; Hiroki Sugiyama; Kazuki Shimojo; Takuro Imaoka; et al. (PLoS ONE)
Objective To clarify the association of detailed angiographic findings with in-hospital outcome after primary percutaneous coronary intervention (p-PCI) for ST-elevation myocardial infarction (STEMI) in Japan. Background Data regarding the association of detailed angiographic findings with in-hospital outcome after STEMI are limited in the p-PCI era. Methods Between January-2004 and December-2018, 1735 patients with STEMI (mean age, 68.5 years; female, 24.6%) who presented to the hospital in the 24-hours after symptom onset and underwent p-PCI were evaluated using the disease registries. The registry is an ongoing, retrospective, single-center hospital-based registry. Results The 30-day mortality rate and in-hospital mortality rate were 7.7% and 9.2%, respectively. Independent predictors of in-hospital mortality were ejection fraction (EF) < 40% [adjusted Odds Ratio (aOR), 4.446, p < 0.001], culprit lesions in the left coronary artery (LCA) (aOR, 2.940, p < 0.001) compared with those in the right coronary artery, Killip class > II (aOR, 7.438; p < 0.001), chronic kidney disease (CKD) (aOR, 4.056; p < 0.001), final thrombolysis in myocardial infarction (TIMI) grades 0/1/2 (aOR, 1.809; p = 0.03), absence of robust collaterals (aOR, 17.309; p = 0.01) and hypertension (aOR, 0.449; p = 0.01). Conclusions Among the consecutive patients with STEMI, the in-hospital mortality rate after p-PCI significantly improved in the second half. Not only CKD, Killip class > II, and EF < 40%, but also the angiographic findings such as culprit lesions in the LCA, absence of very robust collaterals, and final TIMI grades <3 were associated with an increased risk of in-hospital mortality.